Prostaglandins in Induction of Labour - Harsh Shah (National Journal of Medical Research, 2022)
Prostaglandins are naturally occurring hormones that play a significant role in the commencement of labour. Prostaglandins have been utilised in clinical practise to ripen the cervix and elicit uterine contractions synthetically since the 1960s. When a woman's cervix is immature (when her Bishop score is less than six), they are more likely to utilise them. Cervical ripening and labour induction are aided by prostaglandins, which work on cervical collagen to relax and dilate the cervix in anticipation of giving birth. It's possible that prostaglandins have a role in inducing uterine contractions. The benefits of prostaglandins in inducing labour are discussed in this article.